PECULIARITIES OF JUNIOR BALLROOM DANCERS’ MOTIVATION - Ušpurienė, Aistė Barbora (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
The aim of this research is paid to the peculiarities of junior ballroom dancers’ motivation. The sample of the research consisted of 70 12-15-aged junior ballroom dancers – 40 girls and 30 boys. The sport motivation scale (SMS) was chosen in order to reveal this issue. The study revealed that the internal motivation of junior dancers was expressed more than the external motivation, but some statements that reflect the internal motivation were evaluated differently by the dancers. The dancers did not have a strong opinion – they doubted the statements of the external motivation subscales. The dancers mostly disagreed with the following statements: I dance because my friends and other people respect and appreciate me for it and I dance because I think it’s one of the best ways to make friends and communicate. The amotivation of the dancers was not strongly expressed. They did not doubt their success, why they were dancing and they had no thoughts that they will not achieve their intended purpose. The girls that dance ballroom dances have higher internal motivation – to find out and internal motivation – experience; meanwhile, the boys had stronger internal motivation – to strive for perfection. It was also revealed the external motivation – to get identified and coincide – was important for the junior dancers of the both groups.